2014
DOI: 10.1155/2014/647143
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Proteomics Analysis of Altered Protein Expression in the Placental Villous Tissue of Early Pregnancy Loss Using Isobaric Tandem Mass Tags

Abstract: Many pregnant women suffer miscarriages during early gestation, but the description of these early pregnancy losses (EPL) can be somewhat confusing because of the complexities of early development. Thus, the identification of proteins with different expression profiles related to early pregnancy loss is essential for understanding the comprehensive pathophysiological mechanism. In this study, we report a gel-free tandem mass tags- (TMT-) labeling based proteomic analysis of five placental villous tissues from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 54 publications
1
12
0
Order By: Relevance
“…and Ni et al. , although the functions of most proteins are in common between our study and each of the other. The differences might be because we used TMT labeling based proteomics analysis, while Liu et al.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…and Ni et al. , although the functions of most proteins are in common between our study and each of the other. The differences might be because we used TMT labeling based proteomics analysis, while Liu et al.…”
Section: Discussionsupporting
confidence: 56%
“…They found 51 differentially expressed proteins, of which 22 proteins were upregulated and 29 proteins were downregulated, including glutathione S‐transferase mu 2 (GSTM2), BC1 (ubiquinol‐cytochrome c reductase) synthesis‐like (BCS1L), and cullin 7 (CUL7). Moreover, they used pathway analysis and demonstrated that these differentially expressed proteins participated in cell migration, angiogenesis, oxidative stress, apoptosis, and metabolism pathways . Given the inconsistences between the abovementioned two studies, the molecular signaling pathways associated with EPL require further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…The aliquots were then combined, and the pooled samples were evaporated in a vacuum. Strong cation-exchange chromatography (SCX) fractionation was performed using an UltiMate 3000 high-pressure liquid chromatography (HPLC) system as previously described elsewhere (15)(16)(17). A total of 21 fractions were collected at 2-minute intervals over the SCX gradient and sequentially detected on an LTQ Orbitrap Velos (Thermo Fisher Scientific) using the data-dependent acquisition mode.…”
Section: Tandem Mass Tag Labeling Scx Fractionation and Ms Analysismentioning
confidence: 99%
“…A total of 21 fractions were collected at 2-minute intervals over the SCX gradient and sequentially detected on an LTQ Orbitrap Velos (Thermo Fisher Scientific) using the data-dependent acquisition mode. The MS3 method was programmed as described in our previous studies (15)(16)(17).…”
Section: Tandem Mass Tag Labeling Scx Fractionation and Ms Analysismentioning
confidence: 99%
“…In a more recent study, a gel-free TMT-labeling processing followed by LC-MS/MS proteomic of five placental villous tissues from women with early pregnancy loss has resulted in the identification of 51 differentially expressed proteins compared to normal placentas. The identified proteins were mainly involved in cell migration, RNA metabolism, cell differentiation, proliferation, metabolism and apoptosis, as well as reactive oxygen species generation and oxidative stress (129). Several proteomic studies have been conducted in search of early, fetal markers of aneuploidies.…”
Section: Proteomics and Art Outcomementioning
confidence: 99%